Aktivitas Antiobesitas Ekstrak Etanol Daun Kemuning (Murraya paniculata (L.) Jack) pada Tikus Betina Galur Wistar: Antiobesity Activity of Kemuning Leaf Ethanol Extract (Murraya paniculata (L.) Jack) in Female Wistar Rats - Deden Winda Suwandi; Josep Bahari; Anas Subarnas (Jurnal Sains dan Kesehatan, 2023)
Obesity is a condition where there is excessive accumulation of fat due to an imbalance in energy intake with long-term energy expenditure. Serious clinical conditions are often experienced by obese people causing high morbidity and mortality rates at a young age. Efforts to treat obesity pharmacologically are carried out by using synthetic substances that act centrally or peripherally. In addition, many people use natural ingredients that are empirically efficacious in reducing obesity. The aim of this study was to determine the anti-obesity activity of the ethanol extract of Murraya paniculata leaves in female Wistar rats. The test was initiated by induction of animal obesity by subcutaneous administration of monosodium-L-glutamate 2 g/kgbw of rats for the first 5 days and high-carbohydrate diet for 45 days. Parameters observed were body weight, food intake, consistency and weight of faeces, and liver index. The results showed that the ethanol extract of kemuning leaves at doses of 200, 400 and 800 mg/kg of rats has anti-obesity activity by suppressing the increase in body weight of the rats which was significantly different from the positive control (p